Pengembangan Sistem Informasi Pelayanan Publik Digital Berbasis Website di Kelurahan Pontap Kota Palopo - Arfanita Indriyani Arifin; Isdayani B.; Sahrir Sahrir (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Public services are one of the essential functions of village-level government as they are directly related to the needs of the community. However, in Pontap Village, Palopo City, service processes are still carried out manually, which often leads to obstacles such as service delays, difficulties in record-keeping, and limited access to information for residents. This study aims to design and develop a web-based public service information system to improve the efficiency and quality of services at the village office. The system was developed using the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The system was built using the PHP programming language with the Laravel framework and utilizes MySQL as the database which is managed using HeidiSQL. System modeling was carried out using use case diagrams and activity diagrams, while testing was conducted using the black-box testing approach to ensure that all functions operate according to specifications. The resulting system provides community complaint services, administrative letter services, and information on health service schedules such as posyandu and puskesmas activities. It is expected that this system will facilitate residents in accessing information, accelerate service processes, and improve data accuracy through an integrated digital platform. This research is expected to serve as a solution to support the digitalization of public services in Pontap Village and to become a reference for the development of similar systems in other regions.